2005
DOI: 10.1093/aje/kwi095
|View full text |Cite
|
Sign up to set email alerts
|

Young Age at First Sexual Intercourse and Sexually Transmitted Infections in Adolescents and Young Adults

Abstract: The authors examined the relation between age at first vaginal intercourse and a positive nucleic acid amplification test for sexually transmitted infection (STI). A nationally representative sample of 9,844 respondents aged 18-26 years was tested for chlamydial infection, gonorrhea, and trichomoniasis in wave 3 (2001)(2002) of the National Longitudinal Study of Adolescent Health. The authors used multiple logistic regression to assess the relation between age at first sexual intercourse and these STIs and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
301
5
17

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(338 citation statements)
references
References 39 publications
(49 reference statements)
15
301
5
17
Order By: Relevance
“…A diferencia de otros estudios en j贸venes de Estados Unidos, en los que se demostr贸 una asociaci贸n significativa entre la presencia de infecci贸n y las conductas sexuales de riesgo (42,44), y en otro de casos y controles en mujeres cubanas de 15 a 49 a帽os infectadas con C. trachomatis (45), en este estudio no se logr贸 demostrar una asociaci贸n entre conductas de riesgo como el inicio temprano de la actividad sexual, un mayor n煤mero de compa帽eros, la volubilidad en el uso del cond贸n y la infecci贸n por C. trachomatis. Esto tampoco se pudo demostrar en otras investigaciones como el estudio multic茅ntrico de prevalencia en mujeres de cuatro continentes (4), o como los llevados a cabo en adolescentes chilenas (32,33), en j贸venes argentinos (30) y en mujeres de Bogot谩 (43).…”
Section: Resultsunclassified
“…A diferencia de otros estudios en j贸venes de Estados Unidos, en los que se demostr贸 una asociaci贸n significativa entre la presencia de infecci贸n y las conductas sexuales de riesgo (42,44), y en otro de casos y controles en mujeres cubanas de 15 a 49 a帽os infectadas con C. trachomatis (45), en este estudio no se logr贸 demostrar una asociaci贸n entre conductas de riesgo como el inicio temprano de la actividad sexual, un mayor n煤mero de compa帽eros, la volubilidad en el uso del cond贸n y la infecci贸n por C. trachomatis. Esto tampoco se pudo demostrar en otras investigaciones como el estudio multic茅ntrico de prevalencia en mujeres de cuatro continentes (4), o como los llevados a cabo en adolescentes chilenas (32,33), en j贸venes argentinos (30) y en mujeres de Bogot谩 (43).…”
Section: Resultsunclassified
“…We consider heavy use of controlled substances a risky behavior because it puts adolescents at greater risk for developing health problems and addictions, and we deem early sexual intercourse risky behavior because adolescents who have sex at young ages are at greater risk of pregnancy and sexually transmitted diseases than those who delay the onset of sexual intercourse (Kaestle et al 2005). Our delinquency and violence measures are based on a series of questions that measure the frequency of different delinquent or violent behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier first sexual intercourse (FSI) is associated with unprotected intercourse, 1 inconsistent contraceptive use, 2 and multiple partners and with negative social and health outcomes, including partner violence, 3 lower educational attainment, 4,5 unintended pregnancy, teenage parenting, 6 and sexually transmitted infection. 7,8 Definitions of "early" FSI have varied, and include age 15 years and younger 2,4,9 or 16 years and younger, 7,10 or quartiles or tertiles of age at FSI in a study population. 11,12 Previous prospective studies have demonstrated that a range of biological, social, and psychological precursors such as early puberty, childhood adversity, low socioeconomic status, dysfunctional family relationships, absence of a biological father at home, poor school adjustment, adolescent depression, and low self-esteem are associated with earlier age at FSI.…”
Section: What This Study Addsmentioning
confidence: 99%